Kant on human dignity - Sensen, Oliver (Kantstudien. Ergänzungshefte, 2011)
"Kant is often considered the source of the contemporary idea of human dignity, but his conception of human dignity and its relation to human value and the requirement to respect others have not been widely understood. Kant on Human Dignity offers the first in-depth study in English of this subject. Based on a comprehensive analysis of the relevant passages in Kant as well as an analysis of the famous arguments for a value of human beings in the Kant literature, the book provides a thorough interpretation of Kant's conception of human dignity that brings out the unity of Kant's moral thought"--EBL.